Transforming Lives through save the soil mission - Awasthi, U. S.; Tiwari, K. N. (Indian Farming, 2016)
Through the Save the Soil mission, IFFCO has been able to curb the injudicious use of fertilizers by the farmers. As unbalanced use of fertilizers without organic input has created problems of nutrient mining, multiple nutrient deficiency, deterioration in soil health, stagnation in crop productivity etc. Under the mission, regular visit of IFFCOs field executives to the villages helped farmers to understand and adopt modern technologies alongwith indigenous knowledge for sustainable, high yield agriculture.